(untitled) (Biological Sciences - PJSIR, 2010)
Natural dye was extracted from walnut bark and applied on grey split leather for colour measurement study. Premordanting method of dyeing was used with different concentrations of dye at different temperatures for an interval of 45 minutes. Dyed leathers were subjected to colour measuring system and the tristimulus values (XYZ), ANLAB values (LAB) and Munsell renotations (hue, lightness and chroma) were noted. Acetic acid, formic acid, citric acid and tartaric acid were used as mordants before dyeing. Tartaric acid showed best results relating to colour measurements.